Wireless Emergency robot and Assistant with arm - Wael Jaber; Hala Jaber; Obada Abulail (My University, 2022)
Our report is for presenting two technology which when combine together can form and tremendous useful devices for defense system and ultimately society because robot is an unique technology to serve society in different application and in different field so we all knows important of robot now days in society and developing technology the number of robots Used worldwide is constantly increasing. They are more and more present in different workplaces such as, dangerous areas, processing operations,, medical environments, military, manufacturing inaccessible areas etc…….again we have one unique communication technology now that is IOT this report will explain mostly IOT technology because IOT is not only just an technology it is an is phenomenal …Now the Internet is being used to connect various objects such as cars, sensors, controllers, TVs, machinery, transport containers and electrical appliances, creating the Internet of Things (IOT). The networked and user interfaced robots, such as rescue robots, human assisting robots, health care robots and robots for military applications The evolution and growth of the Internet because a technology we can control robot with high distance, high speed and high accuracy. , solution on all communication and controlling over internet which is totally wireless and we can optimistically look forward to an IOT-assisted world that is connected, smarter – and better . This project report describes the robot had been built using two microcontrollers (esp32cam+esp32) and how it can be controlled and powered in the main tuning condition. Also, in this project wireless emergency robot and assistant with arm technology had been used to implement our vision on our robot, it was controlled from a mobile application , to move it or to get some objectives transferred from allocation to another with an access on the camera mounted on it, and the user had been able to reach safety movement restrictions, and also using the arm to do some dangerous thing and assistant on behalf of humans. So, the microcontrollers had been used to control servo motors, DC gear motors, and to view the camera. Webpage and control page of Robot will be built using HTML, CSS and Arduino language. And will be used to send the command from mobile app to the microcontrollers over the cloud